Ultrastructural changes in the tibial regenerate of animals in conditions of anthropogenic microelementosis of the organism and their correction with Dialipon - Korenkov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
Ultrastructural changes in tibial regenerate cells of mature and old rats in conditions of consumption of high doses of heavy metal salts by the animals were studied with help of the method of transmission electron microscopy. In experimental conditions, dystrophic and destructive changes of osteoblast organelles were observed, and there were lower calcium and phosphorus levels in the regenerate bone part, this fact being confirmed by an x-ray microanalysis. A possibility to correct the revealed changes with an antioxidant drug Dialipon was found out.